Implementasi Sistem Monitoring Tandon Air Warga Dusun Sidasari Desa Sidabowa Kecamatan Patikraja Kabupaten Banyumas - Indriyanto, Slamet; Leksono, M. Lukman (Madani : Indonesian Journal of Civil Society, 2025)
Residents of Dusun Sidasari RT.7 RW.01 Sidabowa Village, Patikraja District, Banyumas Regency use a shared water tank to store water from wells to meet their clean water needs. The problem faced by these residents is that there is often a water deficit in the reservoir so the water in the reservoir runs out without the residents knowing. This happens because if there is a pipe leak that is not known by the residents, this has an impact on the work of the pump machine which works extra hard, resulting in the pump machine being damaged several times. Therefore, in this Community Service activity, a Water Reservoir Monitoring System has been implemented. This system will monitor the condition of the water tank. Residents can monitor these conditions through a display on a mobile application so that residents can find out if there is a water deficit in the water reservoir. The output of this activity is an increase in the insight and knowledge of RT administrators and residents regarding technology, accompanied by the installation of devices that have been implemented. The problem of water deficit in the reservoir was successfully overcome through the implementation of monitoring technology. This system allows residents and RT administrators to monitor water conditions in real time, making it easier to identify and anticipate water shortages. Tracking data for 1 week shows increased management efficiency, with the tank filled more than 75% and the empty rate reduced significantly. This success reflects the effectiveness of the system in preventing water deficits. This shows that the community's enthusiasm for this technology also supports better water management. The early detection offered allows monitoring of water conditions in their environment to be met without any obstacles.